Removal of colour from landfill by solar photocatalytic - Salwa, Mohd Zaini Makhtar; Ibrahim, N.; Mohammad Tamizi, Selimin (Asian Network for Scientific Information, 2011)
Link to publisher's homepage at http://ansinet.com/